As relações retóricas e a articulação de dispositivos e de orações no Capítulo I da Constituição Brasileira de 1988 - Angelica Alves Ruchkys (2014)
This work aims at investigating the compositional structure of the legal provisions of one of the sections of the 1988 Brazilian Constitution Law, Chapter I, named Collective Rights and Duties, inserted in a broader section, TITLE II named Fundamental Rights and Guarantees. This investigation is carried out under the perspective of an articulation established between these provisions and their respective clauses or sententional complexes focusing, thus, on the core of the juridical text within which there are normative statements whose starting and ending boundaries are marked by specific graphical signals. The present study is carried out according to the theoretical and methodological framework provided by Halliday on the processes of clause combining and the Rhetorical Structure Theory (RST).Anchored in such theoretical framework, this work verifies not only the net of rhetorical relations of the corpus but also the syntactic aspects of these relations, on the interclausal level. A top down orientation of analysis was adopted (BUTLER, 2005) in which the focus starts from the highest levels of the macrostructure to the successively lowest levels of the microstructure. Underlying the norms analyzed, a basic conceptual scheme was identified, consisting of a set of the most general possible topics. On top of that topic framework, identified the supertopic "legal equality", from which the other topics are specified subsequently. There are three levels of deployment: the first, the topics "way of application" and "way of expansion," complement the supertopic "legal equality"; the next level, supertopic "legal equality" is developed - internally - by topic "rights"; the third level, the "rights" in turn, is developed by topics " guarantee " and "restrictions". In order to investigate the way such units are manifested on the sententional level, the dispositions which contained a single informational unit were distinguished from the ones which had more than one unit. The analysis has confirmed, in the microstructure, the hierarchy between the topics of the basic textual scheme derived from the highest levels of the macrostructure, as the topics regarded as subsidiaries of the most central topics of the scheme constituted the ancillary portion of the nucleus-satellite observed in the several parts of the macrostructure and microstructure. The identification of nucleus-satellite relations between some subparagraphs and paragraphs of the article 5 dispositions which hold syntactic and semantic autonomy- showed that the distribution of the content of the legislations in dispositions allows a peculiar textual processing that conceives satellite portions which do not depend on their nuclei to be comprehended for themselves, although they play specific roles for them. The legal/constitutional dispositions (with the exception of items and sections) composed by dense statements, codified by clauses and sententional complexes, organized under the form of declarations with complete meaning, using Chafes terms - (1980) revealed to be more than formal units, playing a fundamental role in the formal-functional organization of the norms analyzed, considering that it is exactly the way they are conceived that permits the identification of the nucleus-satellite relations between such dispositions, even when they have the same formal configuration, as items of a list.